Real-time discovery of AT2020xnd: a fast, luminous ultraviolet transient with minimal radioactive ejecta. Issue 4 (9th October 2021) - Perley, Daniel A; Ho, Anna Y Q; Yao, Yuhan; Fremling, Christoffer; Anderson, Joseph P; Schulze, Steve; Kumar, Harsh; Anupama, G C; Barway, Sudhanshu; Bellm, Eric C; Bhalerao, Varun; Chen, Ting-Wan; et al.
ABSTRACT: The many unusual properties of the enigmatic AT2018cow suggested that at least some subset of the empirical class of fast blue optical transients (FBOTs) represents a genuinely new astrophysical phenomenon. Unfortunately, the intrinsic rarity and fleeting nature of these events have made it difficult to identify additional examples early enough to acquire the observations necessary to constrain theoretical models. We present here the Zwicky Transient Facility discovery of AT2020xnd (ZTF20acigmel, the 'Camel') at z = 0.243, the first unambiguous AT2018cow analogue to be found and confirmed in real time. AT2018cow and AT2020xnd share all key observational properties: a fast optical rise, sustained high photospheric temperature, absence of a second peak attributable to ejection of a radioactively heated stellar envelope, extremely luminous radio, millimetre, and X-ray emission, and a dwarf-galaxy host. This supports the argument that AT2018cow-like events represent a distinct phenomenon from slower-evolving radio-quiet supernovae, likely requiring a different progenitor or a different central engine. The sample properties of the four known members of this class to date disfavour tidal disruption models but are consistent with the alternative model of an accretion powered jet following the direct collapse of a massive star to a black hole. Contextual filtering of alert streams combined with rapid photometric verification using multiband imaging provides an efficient way to identify future members of this class, even at high redshift.